THE SPEECH ACT OF REFERRING - GERGELY, P. Alpár (Studia Universitatis Babeș-Bolyai Philosophia, 2022)
The Speech Act of Referring. According to the speech-act theory whenever we utter a sentence, we perform two acts: the act of referring and that of predicating. By referring, we set out an object that we speak of, and by predicating, we attribute a feature to the object. My paper is a short presentation of Gottlob Frege’s theory of meaning and Bertrand Russell's theory of description. I will try to outline the core concepts and thoughts/arguments that even today define the debate about reference in the analytic tradition.